Not sure if this is the right place to post, but here goes...

We have been asked to deduce an expression given certain constraints. Now I have deduced a correct expression (i believe) but have been unable to reduce it to the required expression, due to my in experience with the floor and ceiling functions.

My expression for M (given n):

let,

s = floor(sqrt(n))

A = (n - s(s-1) - s) / s

then,

M = 2s + ceiling(A)

The required expression for M:

M = ceiling(2*squrt(n))

any help would be greatly appreciated!!